(untitled) (International Journal of Communication Systems and Network Technologies, 2021)
The aim of this paper is to design an optimal decision maker algorithm for I2SIM using Fuzzy, Neuro fuzzy and Artificial Neural Network (ANN). The objective is to minimize the deaths in the system through controlling the distributor outputs. Three controllers are designed that is able to optimize resource usage following an infrastructure disruption. These controllers are designed in MATLAB and then implemented in I2SIM. From the results, the controller which gives the best distribution output will be determined. The goal of the controller is to maximize an output, which in this case is the number of discharged/healed patients from the hospitals. The results of the controller will be compared and analyzed to determine which technique gives the best result.